The Social Learning Theory Albert Bandura for Elementary School Students - Amsari, Dina; Wahyuni, Etri; Fadhilaturrahmi, Fadhilaturrahmi (Universitas Pahlawan Tuanku Tambusai, 2024)
Learning is a process of interaction between individuals and the environment and is displayed in the form of desired behavioral changes. Learning in schools must be able to bridge the knowledge that students already have with the new knowledge that will be built. This research discusses how Albert Bandura's social learning theory emphasizes the importance of elementary school students in processing their own knowledge obtained from observing models in their environment. This learning theory can be implemented in learning with the assumption that learning can be through observation, learning is an internal process that is reflected in behavior, learning is a reciprocal influence between environmental variables, behavior and individuals, and behavior is goal-oriented and self-regulated. This provides an understanding that learning is the result of students' ability to interpret knowledge or information, interpret a model that is imitated, then process it cognitively and determine actions according to the desired goals. Students are encouraged to think critically and creatively to analyze problems and find alternative solutions to problems.